2019
DOI: 10.2503/hrj.18.173
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Combinations of Apple Cultivars and Storage Technologies for Long-term Storage

Abstract: To improve the year-round supply system for Japanese apple fruit, we selected long-term storable cultivars and assessed optimal storage technologies for them. At first, we investigated the effects of 1-methylcyclopropene (1-MCP) treatment and controlled atmosphere (CA) storage on fruit quality after long-term storage in 30 cultivars. 'Shuyo', 'Sekaiichi', 'Jonagold', 'Kotaro', 'Shinano gold', 'Aori 15', 'Ambitious', and 'Aori 21' were selected for their better quality compared with bagged 'Fuji' stored in CA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Storage performance over a much longer duration than that reported by Onodera et al [51] was reported by Kasai et al [59] to determine which cultivars were resistant to physiological disorders and deterioration of flavor and texture. Apples of 30 cultivars were harvested at their commercial harvest time in the fall and stored under RA, CA, and 1-MCP treatment until mid-June of the next year at 0 • C followed by under RA at 20 • C for 5 days.…”
Section: Watercore During Storagementioning
confidence: 94%
“…Storage performance over a much longer duration than that reported by Onodera et al [51] was reported by Kasai et al [59] to determine which cultivars were resistant to physiological disorders and deterioration of flavor and texture. Apples of 30 cultivars were harvested at their commercial harvest time in the fall and stored under RA, CA, and 1-MCP treatment until mid-June of the next year at 0 • C followed by under RA at 20 • C for 5 days.…”
Section: Watercore During Storagementioning
confidence: 94%